Results of survey on rodents in Phong Nha - Ke Bang national park area, Quang Binh province - Nghia, Nguyen Xuan; Dang, Nguyen Xuan; Luong, Nguyen Duy (Academia Journal of Biology, 2013)
Phong Nha-Ke Bang National Park (PNKB NP), located in Quang Binh Province, with total area of 85,755 ha, has high national and global biodiversity conservation significance. However, rodent fauna in the National Park is poorly studied. Preliminary surveys conducted before 2002 has recorded only 29 species. During 2007 and 2011, we conducted rodent surveys in 4 areas of core zone and expanded zone of PNKB NP: Cha Noi area (17°28’N, 106°06’E) and Hung Dang area (17°38’N, 106°04’E) located in Thuong Trach commune (Bo Trach District); Ma Rinh Moi area (17°42’N, 105°51’E) located in Hoa Son Commune and Hang En area (17°42’N, 105°59’E), located in Thuong Hoa Commune (Minh Hoa District). Totally, 16 survey transects were established with 105,5 km of daytime survey and 60,5 km of night survey were made. Three hundred (300) live traps were used and 4,500 trap.night were made. This survey recorded 32 rodent species, of which 23 species have specimens, 4 species were observed in the wild and 5 species were recorded by hunting specimens and interviewing local residents. The updated list of rodents in PNKB NP consists of 35 species belonging to 5 families (Sciuridae: 11 species, Spalacidae: 2 species, Muridae: 19 species, Hystricidae: 2 species and Laonestidae: 1 species). In comparison with previous list of rodent species in PNKB NP, this study could not find 3 species, however, added 6 other species including the first record of Loatian Rock Rat (Laonastes aenigmamus) in Vietnam. Within 4 flying squirrel species recorded, highest encounter rate belongs to Belomys pearsonii (9.96 individuals/km) and Petaurista philippensis (7.97 individuals/km). Overall trap success of 18 rodent species is 1.949 individuals/100 trap.night and trap success of 8 strict-forest species is almost twice higher than those of 10 not strict-forest species (1.256 vs. 0.692 individuals/100 trap.night). This fact is related to little affected primary forest in the survey areas. There are 6 species of conservation priority including 5 species enlisted in Vietnam Red Data Book (2007), 2 species enlisted in 2012 IUCN Red List and 3 species enlisted in Governmental Decree 32/2006/ND-CP. Rodent fauna in PNKB NP is threatened by illegal wildlife hunting/trapping and forest quality degradation by timber removal.